Exploring Students’ Experience In Using Ai To Assist Their Writing - Eva Fitriani Syarifah; Afief Fakhruddin (English Language Education Department, Universitas Majalengka, 2024)
Artificial Intelligence (AI) has emerged as an effective strategy for helping students improve their writing abilities in today's ever-evolving educational environment. Thus, this study investigates the benefits and applications of using an artificial intelligence assistant to strengthen students' writing skills. Thus, this study aims at investigating the benefits and applications of using an artificial intelligence assistant to strengthen students' writing skills. The data were obtained through observation, questionnaire, and interview. The results of the study revealed that the most commons AI used by the students are Chat GPT, QuillBot, Jenni AI, Grammarly, and StoryAI. The students used AI for different purposes such as for grammar checking, finding story line, getting ideas for the writing topic, and getting first feedback. In line with the results of this study, it can be concluded that AI can be one of the alternatives tools to foster students’ writing skills.